1995
DOI: 10.1159/000126889
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Human Follicle-Stimulating Hormone-β Subunit Gene Expression: GnRH Stimulation and GnRH-Independent Androgen Inhibition

Abstract: Previous studies from our laboratory demonstrated that chronic testosterone administration to castrated transgenic mice suppressed human follicle-stimulating hormone-β (FSHβ) mRNA levels transcribed from a human transgene to approximately 20% of control values. In the present study we used primary pituitary cultures prepared from the transgenic mice and in vivo experiments in hypogonadal (hpg) mice carrying the human transgene to assess the role of hypothalamic gonadotropin-releasing hormone (GnRH) in this inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Primary rat pituitary cultures have been a significant tool, but are not sustainable in culture. Further, although primary rat pituitary cultures in general demonstrate similar regulation to that observed in physiological studies in humans, we have observed some differences among the human FSHβ and mouse FSHβ genes in transgenic animals and the rat FSHβ gene, specifically with regard to androgen regulation (Kumar & Low 1995b). We postulate that the mouse gene may be more comparable to the human gene, making the LβT2 cell line, derived from a mouse pituitary adenoma, a more appropriate model.…”
Section: Discussionmentioning
confidence: 54%
“…Primary rat pituitary cultures have been a significant tool, but are not sustainable in culture. Further, although primary rat pituitary cultures in general demonstrate similar regulation to that observed in physiological studies in humans, we have observed some differences among the human FSHβ and mouse FSHβ genes in transgenic animals and the rat FSHβ gene, specifically with regard to androgen regulation (Kumar & Low 1995b). We postulate that the mouse gene may be more comparable to the human gene, making the LβT2 cell line, derived from a mouse pituitary adenoma, a more appropriate model.…”
Section: Discussionmentioning
confidence: 54%
“…Mice-Gender-specific regulation of gonadotropins has been well studied (68,70,74). To determine if loss of Dicer in gonadotropes affects gonadotropin synthesis and secretion in females similar to males, we first analyzed gonadotropin subunit mRNAs by real time qPCR assays using purified gonadotropes (GFP ϩ ) prepared from the pituitaries of adult female mice.…”
Section: Loss Of Dicer In Gonadotropes Results In Suppressed Gonadotrmentioning
confidence: 99%
“…Isolation of Gonadotropes by Fluorescence-activated Cell Sorting-Pools of pituitaries from 3-4 adult mice of identical genotypes were surgically resected and enzymatically dispersed using collagenase treatment at 37°C as described (70). The final cell suspension was filtered through 100-m nylon cap-containing tubes (BD Biosciences) to remove cell clumps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pituitary cultures from transgenic mice bearing a 10-kb human FSHB minigene (discussed above), androgens suppress both FSH release and human FSHB mRNA levels (the endogenous murine Fshb mRNA levels were too low to measure in the assays used at the time) (240). In vivo studies with GnRH-deficient men similarly suggest a suppressive effect of androgens on FSH release mediated at the pituitary level (241)(242)(243).…”
Section: Steroid Regulation Of Fshbmentioning
confidence: 99%